Language means of expressing emotiveness in advertising discourse (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to the linguistic means of expressing emotion advertising discourse. This type of discourse allows us to consider a special linguistic phenomenon, widely reflecting life and the system of cultural values of the society. Analyzes the explicit and implicit linguistic units expressing emotiveness advertising discourse. Considered in detail the potential emotive advertising slogan as emotive means, as a rule, it is concentrated in the structure of the component advertisement. Intellectual and emotional image of the advertising discourse is most often created through metaphor. The article describes how associativity metaphor evokes positive emotions in consumers. To emotionally rich linguistic tools include theepithets that assess the object and create a vivid image of the product, is better remembered by consumers. The article also analyzes the effect and impact of emotive advertising comparisons and phraseology, are examples of dialogic forms of advertising, which represents the seriocomical confrontation. Thus, it is proved that emotiveness integral part of the advertising discourse.
Keywords: emotional (emotional); advertising discourse; metaphor; image; positive emotions; slogan; impact; linguistic means